Genomic analysis in chemotherapy-naïve prostate cancer prior to PSMA-targeted treatment - Amghar, Mariam; Roscher, Mareike; Rausch, Tobias; Özgür, Hilal; Bauder-Wüst, Ulrike; Bruchertseifer, Frank; Morgenstern, Alfred; Beneš, Vladimír; Kratochwil, Clemens; Benešová-Schäfer, Martina (Frontiers in Oncology, 2026)
IntroductionChemotherapy is typically administered prior to consideration of tandem [225Ac]Ac-/[177Lu]Lu-PSMA-617 therapy in metastatic castration-resistant prostate cancer (mCRPC), making chemotherapy-naïve patients who undergo tandem radionuclide treatment extremely rare. The genomic mechanisms dictating response and resistance to prostate-specific membrane antigen–radiopharmaceutical therapy (PSMA-RPT) in this setting remain unclear. While tandem therapy is expanding for aggressive disease, baseline genomic predictors of treatment outcomes are not well defined. We present rare chemotherapy-naïve mCRPC cases treated with tandem PSMA-RPT and explore their molecular characteristics through plasma circulating tumor DNA (ctDNA).MethodsBlood samples were obtained from mCRPC patients receiving [225Ac]Ac-/[177Lu]Lu-PSMA-617 therapy. Cell-free DNA (cfDNA) was isolated and analyzed using ultra-low pass whole-genome sequencing (ULP-WGS). Genome-wide copy number alterations (CNAs) and tumor fraction (TFx) were inferred with the ichorCNA algorithm.ResultsThis case series included five chemotherapy-naïve patients—four with baseline characterization and one with longitudinal follow-up—providing a rare window into cfDNA CNAs at treatment initiation. Recurrent alterations included amplifications in chromosomes 1q, 7q, and 8q, and losses in 8p. Additional events such as 12q amplification and partial 9q gain were also observed. In Patient 5, serial cfDNA analysis demonstrated stable 8p loss and 8q gain across multiple treatment cycles, despite clinical progression, suggesting clonally persistent genomic drivers.DiscussionBaseline cfDNA CNA profiling in chemotherapy-naïve mCRPC reveals recurrent chromosomal imbalances—particularly 8p loss and 8q gain—that may represent intrinsic, stable features of advanced disease. These findings highlight the exploratory potential of cfDNA-based genomics in rare PSMA-RPT cohorts.